2014
DOI: 10.1136/gutjnl-2013-306253
|View full text |Cite
|
Sign up to set email alerts
|

CCL20/CCR6-mediated migration of regulatory T cells to theHelicobacter pylori-infected human gastric mucosa

Abstract: BackgroundHelicobacter pylori-induced peptic ulceration is less likely to occur in patients with a strong gastric anti-inflammatory regulatory T cell (Treg) response. Migration of Tregs into the gastric mucosa is therefore important.ObjectiveTo identify the homing receptors involved in directing Tregs to the gastric mucosa, and investigate how H pylori stimulates the relevant chemokine responses.DesignGastric biopsy samples and peripheral blood were donated by 84 H pylori-infected and 46 uninfected patients. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
111
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 45 publications
7
111
0
8
Order By: Relevance
“…Furthermore, it has been recently shown that H. pylori infection downregulates the expression of the T cell co-inhibitory molecule B7-H1 in gastric epithelial cells in a CagA-dependent manner, which might contribute to the hyporesponsiveness of CD4(+) effector T cells and accumulation of Tregs 94. Also, H. pylori infection has been shown to induce the production of the chemokine CCL20 in gastric epithelial cells via cag pathogenicity island-dependent nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signalling, a phenomenon believed to be involved in Tregs homing to the gastric mucosa as the majority of Tregs express its receptor CCR6 95 . H. pylori strains expressing CagA represent 60–70% of Western strains and approximately 100% of East-Asian strains 96.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been recently shown that H. pylori infection downregulates the expression of the T cell co-inhibitory molecule B7-H1 in gastric epithelial cells in a CagA-dependent manner, which might contribute to the hyporesponsiveness of CD4(+) effector T cells and accumulation of Tregs 94. Also, H. pylori infection has been shown to induce the production of the chemokine CCL20 in gastric epithelial cells via cag pathogenicity island-dependent nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signalling, a phenomenon believed to be involved in Tregs homing to the gastric mucosa as the majority of Tregs express its receptor CCR6 95 . H. pylori strains expressing CagA represent 60–70% of Western strains and approximately 100% of East-Asian strains 96.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of HP-NAP might also be involved in priming of T cells to a proinflammatory phenotype (Amedei et al, 2006). Infiltrating T lymphocytes have been reported to be recruited to the gastric mucosa via CCL20 binding to their CCR6 chemokine receptors (Cook et al, 2014;Wu et al, 2007), via L-selectin receptors (CD62L) binding to peripheral lymph node addressin (PNAd) (Kobayashi et al, 2004), and via ␣ 4 ␤ 7 integrins, which are known to bind to MAdCAM-1 adhesion molecules expressed by endothelial cells in the gastrointestinal tract (Michetti et al, 2000;Quiding-Järbrink et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…These STAT3-deficient DCs are more potent activators of T cells and have a high capacity to induce Th1 responses [28]. Indeed, several studies have determined that H. pylori -stimulated DCs promote the development of Tregs in vitro [4,5,6,27] and an increase in infiltrating Tregs has been detected in murine models of infection [4,5] as well as in the gastric mucosa of infected humans [33]. Of interest, an increase in Tregs is detected in the gastric mucosa of H. pylori -infected subjects with gastric adenocarcinoma in comparison with H. pylori -mediated chronic gastritis or dysplasia [34].…”
Section: Discussionmentioning
confidence: 99%